Is screening for psychosocial risk factors associated with mental health care in older adults with cancer undergoing surgery?. Issue 3 (18th October 2019) - Trevino, Kelly M.; Nelson, Christian J.; Saracino, Rebecca M.; Korc‐Grodzicki, Beatriz; Sarraf, Saman; Shahrokni, Armin
Abstract : Background: Surgery is a notable stressor for older adults with cancer, who often are medically and psychosocially complex. The current study examined rates of preoperative psychosocial risk factors in older adults with cancer who were undergoing elective surgery and the relationship between these risk factors and the provision of mental health services during the postoperative hospitalization. Methods: A total of 1211 patients aged ≥75 years who were referred to the geriatrics service at a comprehensive cancer center were enrolled. Patients underwent elective surgery with a length of stay of ≥3 days and were followed for at least 30 days after surgery. A comprehensive geriatric assessment was administered as part of routine preoperative care. Bivariate relationships between demographic and surgical characteristics and the preoperative comprehensive geriatric assessment and the receipt of mental health services during the postoperative hospitalization period were examined. Characteristics with bivariate relationships that were significant at the level of P < .10 were entered into a multivariable regression predicting postoperative mental health service use. Results: Approximately one‐fifth of the total sample (20.6%) received postoperative mental health services. In multivariable analyses, high distress ( P = .007) and poor social support ( P = .02) were found to be associated with a greater likelihood of the receipt of mental health services. Of those patients with high distress and poor social support, only approximately one‐quarter (24.6%‐25.5%) received mental health care. Conclusions: Distressed older adults and those with low levels of support preoperatively were found to be more likely to receive mental health services after surgery. Nevertheless, less than one‐third of these patients received inpatient postoperative mental health care, indicating that barriers to translating screening into the provision of psychosocial services remain. Abstract : In older adult patients with cancer who are undergoing elective surgery, preoperative high distress and poor social support are associated with a greater likelihood of the receipt of mental health services during the postoperative hospitalization period. However, in the current study, only approximately 25% of patients with high distress and low social support are found to receive mental health care postoperatively.